Experience with sitagliptin (the first DPP-4 inhibitor) application to the treatment of type 2 diabetes mellitus in the Russian Federation:Results of the DIA-DA observation program - Marina Vladimirovna Shestakova (Сахарный диабет)
This paper reports results of the DIA-DA observation program designed to study the efficacy and safety of the DPP-4 inhibitor sitagliptin added tometformin therapy in different regions of the Russian Federation. The study included 923 patients with DM2 (mean duration 4.5 years) uncontrolledby diet and metformin monotherapy. They were transferred to the combined treatment with sitagliptin and metformin during 6 months. The mainend-points assessed in the study were hypoglycemic efficiency, frequency of side-effects, and satisfaction of patients and physicians with the treatment.The target HbA1c level